Analisis Pengelolaan Limbah Cair pada Pengrajin Batik Besurek di Kelurahan Betungan Kota Bengkulu - Kartika, Aulia; Febriawati, Henni; Oktavidiati, Eva; Wati, Nopia; Angraini, Wulan (Avicenna: Jurnal Ilmiah, 2025)
Background: Bengkulu has besurek batik handicrafts with rafflesia motifs. Betungan Village is one of the areas for making besurek batik in Bengkulu City. Besurek batik here is made using the chemical dyes Naptol, Remasol and Indigasol. Batik waste water is dumped in the gutter so it is dangerous for the environment. Method: The type of research is Qualitative Descriptive. The data collection method was interviews with the Head of Bengkulu City DLH, the head of Santi Batik, members of Santi Batik, residents of Betungan Village and documentation. The research location was in Betungan Batik Village, Selebar District, Bengkulu City. Held for 1 month (March 27 – April 27). Result: The batik waste water service does not distribute it to storage tanks, waste water collection cannot be carried out because processing facilities are not yet available. There is no processing of batik waste water such as storage, absorption, filtering, settling and disposal. Besurek batik craftsmen have not implemented waste water management in accordance with PUPR Ministerial Decree 04 of 2017 concerning the Implementation of a Domestic Waste Water Management System. DLH Bengkulu City collaborated with the Betungan Village Youth Organization to create a miniature wastewater treatment plant. DLH is tasked with providing permits, guidance and supervision. The monitoring of Santi batik waste carried out by DLH is still lacking, it was scheduled to be carried out every 2 months, but this was not achieved. Conclusion: Batik waste water services that are not channeled to storage tanks, without waste water treatment facilities, mean that no waste water treatment can be carried out. Keywords: Service, Collection, Liquid Waste Processing